18=k(3)

Simple and best practice solution for 18=k(3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 18=k(3) equation:


Simplifying
18 = k(3)

Reorder the terms for easier multiplication:
18 = 3k

Solving
18 = 3k

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '-3k' to each side of the equation.
18 + -3k = 3k + -3k

Combine like terms: 3k + -3k = 0
18 + -3k = 0

Add '-18' to each side of the equation.
18 + -18 + -3k = 0 + -18

Combine like terms: 18 + -18 = 0
0 + -3k = 0 + -18
-3k = 0 + -18

Combine like terms: 0 + -18 = -18
-3k = -18

Divide each side by '-3'.
k = 6

Simplifying
k = 6

See similar equations:

| -24x+4x^2=0 | | (3x+72)(x-1)= | | 5x=x+26 | | 12h-18=(4h-6) | | 12x-60=0 | | 6(4y-1)=5 | | 2(x+5)=8 | | 3-n=33 | | x-6=(x-4)1/2 | | y=1.5(1) | | V=dt | | 4x^2-8=20 | | 0=1.5x | | 10(-10x+1)= | | 9n^2-50n-80=0 | | -2a+3(4-a)=-3(a+4)-6 | | V=IxR | | 0.4x^3+0.6x^3-0.3x^3= | | x^2+x+20=0 | | -4m=-32 | | x-7=-20 | | 4x-7x(5x-8)=x-8 | | y=-2(1) | | -4(2z+5)=4 | | 5x+9=11+4x | | j-17=2j+13 | | 5x=3x-18 | | n-3n=14-4 | | d-4d=d+1-4d | | .2x-y=2 | | -18y=9 | | 4x^2y-16xy^2= |

Equations solver categories